Raman Spectroscopy Investigation of Laser-Irradiated Single-Walled Carbon Nanotube Films; Physica Status Solidi (B); Vol. 256, iss. 2 - Rodriguez (Rodriges) Contreras R. D. Raul David (2019, 2019)
Title screen